2017
DOI: 10.1063/1.4989693
|View full text |Cite
|
Sign up to set email alerts
|

Continuously tuneable critical current in superconductor-ferromagnet multilayers

Abstract: We demonstrate that the critical current of superconducting Nb/Ni multilayers can be continuously tuned by up to a factor of three during magnetization reversal of the Ni films under an applied in-plane magnetic field. Our observations are in reasonably good agreement with a model of vortex pinning by Bloch domain walls that proliferate in the samples during magnetization reversal, whereby each vortex interacts with at most one wall in any of the Ni layers. Our model suggests ways in which the controllable pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Thus, a definitive comparison between theory and experiment in superconducting spintronics is problematic without considering the exact strength of stray field. Therefore, it is an important parameter to know in proximity effect based or domain state dominated superconducting spintronic devices 16,17,38,39 . However, no direct quantification of the extent to which a superconducting layer is affected by these stray fields, are available in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a definitive comparison between theory and experiment in superconducting spintronics is problematic without considering the exact strength of stray field. Therefore, it is an important parameter to know in proximity effect based or domain state dominated superconducting spintronic devices 16,17,38,39 . However, no direct quantification of the extent to which a superconducting layer is affected by these stray fields, are available in the literature.…”
mentioning
confidence: 99%
“…Hu et al 24 reported the stray field and the superconducting surface spin valve effect in La 0.7 Ca 0.3 MnO 3 /YBa 2 Cu 3 O 7−δ bilayers. Curran et al 16 have imaged the stray fields at the surface of Nb/Ni multilayer samples at various temperatures using the High resolution scanning Hall microscopy (SHM). Yang et al 25 A series of Nb-Ni bilayer thin films was prepared at room temperature in a vacuum chamber with base pressure in the range of 10 −9 mbar, using dc-magnetron sputtering of high purity(99.999%) niobium and nickel targets on cleaned Si-SiO 2 substrates.…”
mentioning
confidence: 99%
“…Subsequently, Jc was measured by sweeping the magnetic field in the order of +0.5, 0, −0.5, 0, +0.5 T. Jc also exhibits hysteresis, reflecting the magnetic hysteresis of the Co layer. Jc shows a symmetric behavior with respect to zero field (dashed line) for the sweep of the magnetic field in the order of −0.5, 0, +0.5, 0 T. The pronounced peak around the coercive field can be attributed to enhanced vortex pinning on the network of proliferating domain walls 26 .…”
mentioning
confidence: 96%
“…Stray fields emanating from nanomagnet arrays or domain walls provide preferential pinning sites for an Abrikosov vortex, as the type-II superconductor acts to screen the stray fields. By reconfiguring the nano-magnet array or domain wall, it is possible to modify the pinning potential on the vortex, creating multiple states for a memory device [16][17][18][19]. A noteworthy system in which to realise such effects are artificial spin ices, where magnetic frustration provides a rich phase diagram of magnetic configurations [20].…”
mentioning
confidence: 99%
“…Fuelled by advances in hybrid structures, the study of Abrikosov vortices is currently in somewhat of a renaissance [15][16][17][18][19][20]. In addition to the possibility of devices, it would certainly be interesting for future research to address the inverse of the effect studied by Patiño and Blamire-can the Abrikosov vortex state imprint domain walls or spin textures onto an otherwise uniform ferromagnet?…”
mentioning
confidence: 99%